THE ALPHEID SHRIMP OF INDONESIA, BASED UPON J.G. DE MANS "THE DECAPODA OF THE SIBOGA EXPEDITION, PART II. FAMILY ALPHEIDAE." (1911) - Banner, Dora M.; Banner, Albert H. (Marine Research in Indonesia, 1985)
We wish not only to up-date the taxonomy used by DE MAN in his 1911 study but also to add to his list of species those new records of species from Indonesia based, upon collections made subsequently by various individuals and agencies. DE MAN reported that he had 113 species and 20 varieties of these shrimp from the Siboga Expedition; of these, 54 species and varieties have been reduced to synonymy in the subsequent years. In the present study these additional species are also being so reduced:Alpheopsis hummelinki SCHMITT (= Neoalpheopsis euryone (De Man)Neoalpheopsis hiatti BANNER (= N. euryone De Man) Synalpheus jedanensis De Man (= S. iphinoe De Man) S. miscellaneus De Man ( = S. neomeris (De Man) S. physocheles Coutiere (= S. triunguiculatus (Paulson) S. sluiteri De Man (= S. paraneomeris Coutiere) S. stimpsonii var. maldivensis C outiere (= S. stimpsonii ( De Man) S. streptodactytoides De Man (=S. streptodactylus Couti>re)From the post-Siboga collections, we list an additional 28 established species from Indonesian waters as well as two new species: Alpheus nipa and Synalpheus mortenseni; we also have reviewed the status of Alpheus (= Synalpheus) tricuspidatus Heller (1861) and consider it to be a nomen dubium. We now recognize a total of 145 species from Indonesian waters plus an additional 2 species left unnamed by De Man and by us.